Study and Control of a Stepper Motor using an Arduino Card - قرفي, خير الدين; مولاي, ادريس (University of El Oued جامة الوادي, 2018)
العمل المقدم في هذه المذكرة يمثل معارف معمقة حول المحرك الخطوي, كيفية تصنيعه الافتراضي, محاكاته و كيفية التحكم به. هذا المشروع هو عمل تطبيقي يشرح كيفية التحكم في المحرك الخطوي باستعمال لوحة الأردوينو. التحكم في الموضع محقق باستعمال المصحح الطردي- التكامل-المشتق The work presented in this thesis is a deep basic knowledge about a stepper motor, how to modeling, simulates and control of the stepper motor. This project is a practical work that shows how to control a stepper motor using an Arduino card. The position control is achieved using a PID controller.
مذكرة ماسترهندسة كهربائية تخصص تحكم كهربائي
Keywords: Stepper Motor, PID Controller, Arduino card, Position Control.; المحرك الخطوي,المصحح (الطردي, التكامل, المشتق), بطاقة أردوينو, التحكم في الموضع